STATUS TANAH WAKAF YANG BELUM TERDAFTAR BILA TERJADI GUGATAN AHLI WARIS (STUDI DI KECAMATAN UJUNG BATU KABUPATEN ROKAN HULU) - BAMBANG EDRIYANTO (PREMISE LAW JURNAL, 2015)
Since Islam came to Indonesia, wakaf (property donated for religious/community purpose) has been regulated according to the Islamic law (figh). The procedure for wakaf is sufficiently made with a pledge that he donates his property. Since the issuance of the Government Regulation, it has been done in front of PPAIW (official empowered to draw up wakaf pledge), proved by the pledge by the wakif (donor). Registering wakaf land, according to the Agrarian Law, is in a written form which is aimed to get authentic evidence for the person entitled to it. on it should be registered to the Agrarian Directorate Branch Office of District/Town at which PPAIW is required to file a request the registration to the Office for the lands which will be made their certificates in order to avoid dispute in the future. Keyword : Wakaf Land, BPN, Unregistered